2014
DOI: 10.1097/mao.0000000000000472
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Prevalence of and Risk Factors for Tinnitus in a Young Population

Abstract: We believe that understanding the influences of these factors will help in preventing tinnitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 21 publications
6
53
0
11
Order By: Relevance
“…Additionally, subjective hearing loss and bilateral tinnitus showed statistically significant associations with the frequency of tinnitus in a subgroup analysis (Table ). Sleep disturbance has been reported as a risk factor for tinnitus not only in adults, but also in adolescents in previous studies . Consistent with these studies, sleep problems were also associated with tinnitus in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, subjective hearing loss and bilateral tinnitus showed statistically significant associations with the frequency of tinnitus in a subgroup analysis (Table ). Sleep disturbance has been reported as a risk factor for tinnitus not only in adults, but also in adolescents in previous studies . Consistent with these studies, sleep problems were also associated with tinnitus in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…In that study, the locus of control seemed to affect tinnitus severity only indirectly, as partial correlations indicated that this effect was mediated by the locus of control on anxiety and depression. Contrary to popular belief, abuse of alcohol has not been identified as a significant risk factor for tinnitus 17 . A negative association between physical activity and duration of tinnitus has been reported 18 .…”
Section: Introductionmentioning
confidence: 90%
“…Tinnitus, often associated with hearing loss, has been reported in community surveys of young people associated not only with occupational noise exposure but also with other sources of noise exposure [21]. For young people, the risks to hearing are more likely to result from leisure noise from clubs and rock concerts, and recently, there has been concern over sound levels from personal listening devices.…”
Section: Noise-induced Hearing Lossmentioning
confidence: 99%